The Effectiveness of Monitoring Controls and Individual Moral Reasoning in the De-escalation of Commitments - HERLINA RACHMAWATI DEWI; SUPRIYADI SUPRIYADI (The Indonesian Journal of Accounting Research, 2013)
The study examines the impact of two adverse selection elements (private information and incentives to shirk) on managers' escalation of commitment and the effectiveness of monitoring controls and manager's moral reasoning in de-escalating managers' commitment. This study contributes to the accounting literature by comprehensively evaluating the escalation commitment phenomena from its determinants, the strategy to reduce it, and the impact of moral reasoning level on managers' escalation commitment behavior. This research employed laboratory experiment method with 95 participants of undergraduate and graduate students. Consistent with Harrell and Harrison (1994), the findings of this study indicate that managers who experience    adverse selection problems showed greater tendency to continue    unprofitable project than managers who do not have such problems. However, this study fails to provide empirical evidence that monitoring control and individual moral reasoning level affect the tendency of managers to escalate their commitment.